Applications of marine collagens in bone tissue engineering. (2nd April 2021) - Lin, Zhidong; Tao, Yu; Huang, Yue; Xu, Tao; Niu, Wei
Abstract: For decades, collagen has been among the most widely used biomaterials with several biomedical applications. Recently, researchers have shown a keen interest in collagen obtained from marine sources because of its biocompatibility, biodegradability, ease of extractability, safety, low immunogenicity, and low production costs. A wide variety of marine collagen-based scaffolds have been developed for bone tissue engineering, and these scaffolds display excellent biological effects. This review aims to provide an overview of the biological effects of marine collagen in bone engineering, such as promoting osteogenesis and collagen synthesis, inhibiting inflammation, inducing the differentiation of cartilage, and improving bone mineral density. Marine collagen holds great promise as a biomaterial in bone tissue engineering.